1996
DOI: 10.1142/s0218625x96001273
|View full text |Cite
|
Sign up to set email alerts
|

OPTICAL PROPERTIES OF CdS AND Se CLUSTERS IN ZEOLITES

Abstract: We have studied the electronic and vibrational properties of CdS and Se clusters in zeolites by Raman scattering and photoluminescence measurements. CdS clusters were formed photochemically through the dissociation of S 8 molecules in A and X types of Cd 2+-exchanged zeolites by laser irradiation, while CdSe clusters were not successfully produced in the same manner. The 1LO mode of CdS at 300 cm −1 shifts to lower frequencies in the zeolites in comparison with that of bulk CdS , indicating the effect of phono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
1999
1999

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…ahn versus photon energy hn for Se clusters incorporated into a) LTA zeolites and b) FAU zeolites, together with that for bulk a-Se; a is the absorption coefficient in each zeolite. We have found by Raman scattering measurements and reported that the structure of Se clusters is intriguingly affected by the geometrical restriction in the zeolites [9,10]. Se clusters in 3A(K + ) have a helical chain structure or chain-like segment (i.e.…”
Section: Resultsmentioning
confidence: 98%
“…ahn versus photon energy hn for Se clusters incorporated into a) LTA zeolites and b) FAU zeolites, together with that for bulk a-Se; a is the absorption coefficient in each zeolite. We have found by Raman scattering measurements and reported that the structure of Se clusters is intriguingly affected by the geometrical restriction in the zeolites [9,10]. Se clusters in 3A(K + ) have a helical chain structure or chain-like segment (i.e.…”
Section: Resultsmentioning
confidence: 98%